The Elderly Nursing Core Set and the cognition of Portuguese older adults: a cross-sectional study - César Fonseca; Lara Guedes de Pinho; Manuel José Lopes; Maria do Céu Marques; José Garcia-Alonso (BMC, 2021)
Abstract Background The aging population and its associated health needs require specific nursing care. The aim of this study was to draw an epidemiological profile of Portuguese elderly adults attending in residential homes and day centers and to evaluate the association between the functioning and cognition of these older adults and their sociodemographic characteristics and presence of multimorbidity. Methods This was a cross-sectional study of 613 older adults. Functioning was assessed using the Elderly Nursing Core Set, and cognition was assessed using the Mini Mental State Examination. Descriptive and inferential analyses were performed. Results The mean age was 85.73 years; the majority of the participants were female (69.3 %), widowed (67.0 %) and over 85 years old (60.4 %). A total of 68.2 % of the sample presented multimorbidity. A total of 54.5 % had cognitive impairment, and the average functional profile was classified as "moderate difficulty". Institutionalized older adults had more diseases than those who attended the day center. Women, those who were illiterate, those who were institutionalized and older adults who had diseases of the nervous system had a worse functional profile and greater cognitive impairment. Those with multimorbidity had a worse functional profile, and those without a spouse had greater cognitive impairment. Conclusions Given the functional and cognitive profile of older adults, it is necessary to adopt care practices focused on the rehabilitation/maintenance of self-care and affective relationships. This care must be provided by highly qualified professionals. Therefore, it is necessary to increase the ratio of nurses per older adult in these institutions.